Investigating factors associated with success of breastfeeding in first-time mothers undergoing epidural analgesia: a prospective cohort study - Tan, Daryl Jian An (Int Breastfeed J, 2018)
BACKGROUND: We investigated the possible risk factors that could influence the likelihood of breastfeeding at 5 to 9 weeks postpartum with our primary aim being to analyse the associations between psychological vulnerabilities, such as peripartum depression and anxiety, and continued breastfeeding. Our secondary aim was to investigate other non-psychological factors’ influence on continued breastfeeding. METHODS: A prospective cohort study was conducted in KK Women’s and Children’s Hospital in Singapore. Healthy nulliparous parturients at ≥36 weeks gestation with a singleton fetus who received epidural analgesia were recruited. Demographic and anaesthetic data were obtained. Self-reported psychological and pain determinants such as anxiety (State-Trait Anxiety Inventory), depression (Edinburgh Postnatal Depression Scale), stress (Perceived Stress Scale), pain susceptibility (Pain Catastrophizing Scale) and pain perception (McGill Pain Questionnaire) were also recorded at baseline. A phone interview was then performed at 5 to 9 weeks postpartum to obtain information on breastfeeding status. RESULTS: 329 participants were included into this study, of which 263 (79.9%) of them were still breastfeeding at 5 weeks postpartum. Multivariate logistic regression analysis showed that a higher State-Trait Anxiety Inventory score (Adjusted Odds Ratio [AOR] 0.97; 95% Confidence Interval [CI] 0.94, 1.00) at baseline, higher intrapartum blood loss (AOR 0.76; 95% CI 0.61, 0.93), and occurrence of fetal anomalies (AOR 0.15; 95% CI 0.03, 0.72) were associated with reduced likelihood of breastfeeding at 5 to 9 weeks postpartum. Indians (AOR 0.56; 95% CI 0.20, 1.53), Malays (AOR 0.30; 95% CI 0.14, 0.62) and other ethnicities (AOR 0.36; 95% CI 0.16, 0.83) were less likely to continue breastfeeding compared to Chinese participants. On the other hand, receiving any support services on breastfeeding during the participants’ hospital stay was 3.3 times more likely (AOR 3.30; 95% CI 1.21, 9.02) to increase the likelihood of breastfeeding at 5 to 9 weeks postpartum. CONCLUSION: We identified 5 independent association factors that could have significant influences on breastfeeding at 5 to 9 weeks postpartum. Healthcare providers could utilize this risk stratification to identify parturients likely to have poorer breastfeeding outcomes and undertake interventions that may help safeguard optimization of breastfeeding outcomes and parturient care. TRIAL REGISTRATION: Clinicaltrials.gov NCT02278601. Registered 26 October 2014. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13006-018-0184-7) contains supplementary material, which is available to authorized users.